Correlating Electronic Properties of N‐Heterocyclic Carbenes with Structure, and the Implications of Using Different Probes. Issue 2 (12th January 2022) - Barnett, Christopher; Harper, Jason B.; Cole, Marcus L.
Abstract: The σ ‐donating and π ‐accepting properties of a series of N ‐methylimidazolium‐derived N ‐heterocyclic carbenes, systematically altered at the 4, 5‐positions, were determined using two NMR‐based probe techniques. The sterically slight methyl substituent provided reliable probe data, free from through‐space effects, and reliable measures of the electronic properties. Correlations with established electronic parameters for the substituents show that the electronic properties of carbenes, when extraneous effects are controlled for, are indeed predictable. These correlations were compared with earlier data which revealed a previously unrecognised systematic deviation for N ‐aryl substituents. Abstract : Are electronic effects predictable? Yes and no. Changing the 4, 5‐substituents of an N ‐heterocyclic carbene alters its electronic properties in a predictable manner. However, changing the 1, 3‐substituents does not; different outcomes are observed depending on the probe used.